Thai graduate students under the supervision of the Tahi Civil Service Commission in the Philippines a descriptive profile - Wudtipornpong, Wanida 1946- (1970)
The purpose of the study is to develop a descriptive profile of the Thai graduate students in the Philippines who are under the supervision of the Thai Civil Service Commission. Official information about each of the 117 respondents were taken from the Student's Department of the Thai Civil Service Commission. Other information were taken through questionnaires and interviews.
Thesis (M.Ed.)--University of the Philippines, Diliman.
Keywords: Thai students in the Philippines